2011
DOI: 10.1103/physrevlett.106.153901
|View full text |Cite
|
Sign up to set email alerts
|

Granularity and Inhomogeneity Are the Joint Generators of Optical Rogue Waves

Abstract: In the presence of many waves, giant events can occur with a probability higher than expected for random dynamics. By studying linear light propagation in a glass fiber, we show that optical rogue waves originate from two key ingredients: granularity, or a minimal size of the light speckles at the fiber exit, and inhomogeneity, that is, speckles clustering into separate domains with different average intensities. These two features characterize also rogue waves in nonlinear systems; thus, nonlinearity just pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
119
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(128 citation statements)
references
References 21 publications
8
119
0
1
Order By: Relevance
“…Conversely, if randomness mostly arises from the initial field, linear and nonlinear effects occurring inside the propagation medium interplay to modify the statistical properties of the incoherent wave launched as initial condition. This process, extensively studied during the past years, may result in the formation of extreme or rogue waves [2][3][4][5].In this context, the nonlinear Schrödinger equation (NLSE) plays a special role because it provides a universal model that rules the dynamics of many nonlinear wave systems. In the fields of oceanography and laser filamentation, numerical simulations of the NLSE with random initial conditions have been made in 2 þ 1 dimensions to study the emergence of rogue waves [6][7][8].…”
mentioning
confidence: 99%
“…Conversely, if randomness mostly arises from the initial field, linear and nonlinear effects occurring inside the propagation medium interplay to modify the statistical properties of the incoherent wave launched as initial condition. This process, extensively studied during the past years, may result in the formation of extreme or rogue waves [2][3][4][5].In this context, the nonlinear Schrödinger equation (NLSE) plays a special role because it provides a universal model that rules the dynamics of many nonlinear wave systems. In the fields of oceanography and laser filamentation, numerical simulations of the NLSE with random initial conditions have been made in 2 þ 1 dimensions to study the emergence of rogue waves [6][7][8].…”
mentioning
confidence: 99%
“…Since then, optical rogue waves have been observed in several systems [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], and their study has advanced the research in the field, in a way that has been compared to the introduction of optical systems to study chaos in the 1980s [26].…”
mentioning
confidence: 99%
“…Using third 6 harmonic generation microscopy we found that our LH have a prolate spheroid shape with dimensions of 2-3 μm for the transversal semi-principal axes while the longitudinal are approximately 8-10 μm. The lattices inscribed consist of five superposed layers of 400 LH for each layer.…”
Section: Methodsmentioning
confidence: 84%
“…Since sailors are well known story makers these monster, destructive waves that were in naval folklore perhaps for thousands of years penetrated the realm of science only recently and after quantitative observations [1,2]. Since then, they seem to spring up in many other fields including optics [3][4][5][6][7], BEC and matter waves, finance, etc [8][9][10][11][12]. Unique 2 features of rogue waves, contrary to other solitary waves, are both their extreme magnitude but also their sudden appearance and disappearance.…”
Section: Ocean Rogue Waves (Rw) -Huge Solitary Waves-have For Long Trmentioning
confidence: 99%
See 1 more Smart Citation